Chapter 2 Lev Nikolaevich Tolstoy A Queer, Christian-Anarchist Writer - Sethness Castro, Javier (Taylor & Francis, 2023)
This chapter, the book's introduction and summary, examines Tolstoy's life and art using psychobiographical, historical, and sexological prisms. The centrality of erotic non-conformism is the artist's emotional landscape and anarchist vision is emphasized. The numerous precedents in Russian history and society for LGBT life, from medieval legends to the sex-lives of despots and artists alike, are reviewed. An in-depth exploration of Tolstoy's erotic and attachment history, taken together with the number of same-sex relationships portrayed in his art, uncovers an underappreciated erotic dissidence.